Co(II) Coordination in Prokaryotic Zinc Finger Domains as Revealed by UV-Vis Spectroscopy. (14th December 2017) - Sivo, Valeria; D'Abrosca, Gianluca; Russo, Luigi; Iacovino, Rosa; Pedone, Paolo Vincenzo; Fattorusso, Roberto; Isernia, Carla; Malgieri, Gaetano
Abstract : Co(II) electronic configuration allows its use as a spectroscopic probe in UV-Vis experiments to characterize the metal coordination sphere that is an essential component of the functional structure of zinc-binding proteins and to evaluate the metal ion affinities of these proteins. Here, exploiting the capability of the prokaryotic zinc finger to use different combinations of residues to properly coordinate the structural metal ion, we provide the UV-Vis characterization of Co(II) addition to Ros87 and its mutant Ros87_C27D which bears an unusual CysAspHis2 coordination sphere. Zinc finger sites containing only one cysteine have been infrequently characterized. We show for the CysAspHis2 coordination an intense d - d transition band, blue-shifted with respect to the Cys2 His2 sphere. These data complemented by NMR and CD data demonstrate that the tetrahedral geometry of the metal site is retained also in the case of a single-cysteine coordination sphere.